Comparing intercultural competence in lower secondary English and French classrooms in Norway: An overview study - Julie Casoli Uvsløkk; Eva Thue Vold (Moderna Språk)
The purpose of this study is to compare and analyze evidence of intercultural competence across 22 lower secondary English-as-a-second-language and French-as-a-foreign-language classrooms in Norway based on video observations of naturally occurring instruction. We recorded minimum four consecutive lessons in each classroom across two school years, totaling 90 lessons. Research on intercultural competence in second and foreign language classrooms has involved analyses of curricula, textbooks, literary texts in class, and intervention studies, but few scholars have observed naturally occurring instruction. Even fewer studies have used video observations to compare language subjects. This study aims to fill this gap by providing an overview of how intercultural competence is addressed in English and French instruction and identifying similarities and differences between the two subjects. Using the model elaborated in the Reference Framework of Competences for Democratic Culture (RFCDC) as an analytical lens, we found that the model’s area knowledge and critical understanding was most prominent in both subjects and that cultural stereotypes both occurred and were challenged by students across subjects. However, we found more, and more varied, evidence of intercultural competence in the English classrooms, where topics were studied in-depth, whereas the French classes often studied an array of topics more superficially.